Staging Migrations toward an American West : From Ida B. Wells to Rhodessa Jones - Effinger-Crichlow, Marta (Book collections on Project MUSE., 2014)
Staging Migrations toward an American West examines how black women's theatrical and everyday performances of migration toward the American West expose the complexities of their struggles for sociopolitical emancipation. While migration is often viewed as merely a physical process, Effinger-Crichlow expands the concept to include a series of symbolic internal journeys within confined and unconfined spaces. Four case studies consider how the featured women-activist Ida B. Wells, singer Sissieretta ""Black Patti" Jones, World War II black female defense-industry workers, and performance artist